A stabilizing factor?-Video gaming among elite athletes during the first lockdown of the COVID-19 pandemic - Breckwoldt, T.; Fröhlich, S.; Iff, S.; Bitar, R.; Spörri, J.; Scherr, J.; Seifritz, E.; Quednow, B. B.; Claussen, M. C. (Frontiers in Psychology, 2022)
Objectives: Little is known about the extent of video gaming among elite athletes, specifically under stressful conditions like those induced by the current COVID-19 pandemic. The aim of this study was to evaluate the intensity and extent of video gaming in the context of the COVID-19 pandemic, during which the usual daily routine of many athletes was disrupted.